Lessons From the Western Atlantic Lionfish Invasion to Inform Management in the Mediterranean - Ulman, Aylin; Ali, Fadilah Z.; Harris, Holden E.; Adel, Mohammad; Mabruk, Sara A. A. Al; Bariche, Michel; Candelmo, Allison C.; Chapman, Jennifer K.; Çiçek, Burak Ali; Clements, Kaylin R.; Fogg, Alexander Q.; Frank, Stacy; et al. (Frontiers in Marine Science, 2022)
Two major biological lionfish invasions are underway, one in the Western Atlantic Ocean and another in the Mediterranean Sea. The Western Atlantic invasion is the most robustly studied fish invasion to date; meanwhile the lionfish invasion in the Mediterranean is rapidly expanding. Here, we review and synthesize management successes and failures from the Western Atlantic, as well as the current state of management in the more recent Mediterranean invasion, to synthesize policy recommendations. Broadly, the most important management lessons are that (1) directed lionfish removals via spearfishing using scuba can effectively reduce their local abundances and that (2) opportunities exist to develop commercial lionfish fisheries for food and other products that may promote long-term control. In particular, tournaments and derbies can concurrently achieve multiple objectives of promoting lionfish removals, research, and public education. Managers in the Western Atlantic often needed to adapt current conservation policies to enable lionfish removals in areas where spearfishing with scuba were otherwise prohibited for conservation purposes. The risk of abusing these policies has mostly been mitigated through gear restrictions and through direct communication with scuba divers and stakeholder organizations, via participatory approaches, in lionfish monitoring, removals, and management. Two approaches that were initially common but now advised against are (1) feeding lionfish to native fish to promote predation, which led to injurious encounters between divers and marine predators, and (2) implementing bounty programs to incentivize lionfish harvest, which need continuous financial commitments. In the more recently invaded Mediterranean Sea, our review of the current status of policies found that many of these best practice recommendations for lionfish management are not yet permitted under current regulations. Management strategies implemented in Cyprus, however, have been effective in allowing compliant removal of lionfish under the auspices of researchers and environmental agencies. We fully recommend that work continues towards multinational cooperation to facilitate regional coordination of research, control, and management efforts with respect to the Mediterranean lionfish invasion. As with other major biological invasions, lionfish are unconstrained by political borders and their control requires rapid and strategic management approaches with multinational cooperation involving individuals, governments and other stakeholders.